2017
DOI: 10.1002/mrm.27049
|View full text |Cite
|
Sign up to set email alerts
|

Non‐water‐suppressed 1H FID‐MRSI at 3T and 9.4T

Abstract: We showed the first implementation of non-water-suppressed metabolite-cycled H FID MRSI at ultra-high fields. An increase in Cre/NAA was seen for the metabolite-cycled case. The same methodology was further applied at 3T and similar results were observed. Magn Reson Med 80:442-451, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
(68 reference statements)
1
23
0
Order By: Relevance
“…The intra‐subject CVs obtained in this study (Glx/tCr: 9.3%, tNAA/tCr: 6.9%, tCho/tCr: 6.5%, m‐Ins/tCr: 7.8%) were significantly lower than those obtained in the above‐mentioned intra‐session reports. Further improvements in intra‐subject CVs compared to 8–10% in Glx/tCr as observed here can be expected with higher SNR and spectral resolution at ≥7T, potentially enabling functional MRSI studies. Our results also confirm that the use of SHMOCO gives overall significantly better intra‐subject CVs than NOCO, which mainly reflects SHMOCO’s ability to correct for temporal frequency drifts and involuntary subject movements.…”
Section: Discussionmentioning
confidence: 68%
“…The intra‐subject CVs obtained in this study (Glx/tCr: 9.3%, tNAA/tCr: 6.9%, tCho/tCr: 6.5%, m‐Ins/tCr: 7.8%) were significantly lower than those obtained in the above‐mentioned intra‐session reports. Further improvements in intra‐subject CVs compared to 8–10% in Glx/tCr as observed here can be expected with higher SNR and spectral resolution at ≥7T, potentially enabling functional MRSI studies. Our results also confirm that the use of SHMOCO gives overall significantly better intra‐subject CVs than NOCO, which mainly reflects SHMOCO’s ability to correct for temporal frequency drifts and involuntary subject movements.…”
Section: Discussionmentioning
confidence: 68%
“…A next step toward clinical translation could be to combine metabolite cycling with cardiac echo‐planar spectroscopic imaging . Metabolite cycling has already been combined with spectroscopic imaging for brain applications, but the transition to the heart has not yet been made.…”
Section: Discussionmentioning
confidence: 99%
“…The L2 method was shown to allow reconstruction of metabolic images even from the LTE‐NWS‐MRSI data with metabolic images generally close to those from the LTE‐WS‐MRSI. Several previous studies have demonstrated the feasibility of in vivo non‐water‐suppression MRSI with metabolite and water signals measured simultaneously . Advantages of this approach include the availability of the full water signal for eddy current correction and use an internal reference for metabolite quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated the feasibility of in vivo non-water-suppression MRSI with metabolite and water signals measured simultaneously. [37][38][39][40][41][42] Advantages of this approach include the availability of the The limits of agreement are calculated as mean ± 1.96 standard deviation and shown on each plot (dashed lines). The solid line represents the mean of the measurement differences full water signal for eddy current correction and use an internal reference for metabolite quantification.…”
Section: Discussionmentioning
confidence: 99%